2023
DOI: 10.1021/acs.langmuir.2c02662
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Mechanical Properties of 3D Printed Nanocomposites with Varied Particle Diameter

Abstract: 3D printed nanocomposites provide a method for generating high-performance radio frequency devices. Limited work has been done to investigate the influence the nanoparticle diameter has on the performance of 3D printable nanocomposites. We describe here the development of a family of 3D printable nanocomposite inks formulated from nanoparticles with diameters ranging from 30 to 300 nm. Relative permittivity values for the printed nanocomposites were unaffected by nanoparticle diameter whereas loss tangent, gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The hydrogel printed by this ink has cross-linking between nanoparticles triggered by light curing in addition to non-covalent force, which has stronger mechanical properties and memory properties than the hydrogel produced by simple non-covalent or cross-linking and has a wide range of tissue engineering application prospects. [125] Some studies have also found that nanoparticles of different particle diameters [132] and shapes can affect the mechanical properties of materials. Besides, researchers often use metal nanoparticles to enhance the mechanical properties of polymer materials, [133] such as Fe 2 O 3 nanoparticles, [134] gold nanoparticles, [135,136] ZrO nanoparticles, [137] titanium dioxide nanoparticles [138] and CuS nanoparticles.…”
Section: Nanomaterials For Enhancing Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogel printed by this ink has cross-linking between nanoparticles triggered by light curing in addition to non-covalent force, which has stronger mechanical properties and memory properties than the hydrogel produced by simple non-covalent or cross-linking and has a wide range of tissue engineering application prospects. [125] Some studies have also found that nanoparticles of different particle diameters [132] and shapes can affect the mechanical properties of materials. Besides, researchers often use metal nanoparticles to enhance the mechanical properties of polymer materials, [133] such as Fe 2 O 3 nanoparticles, [134] gold nanoparticles, [135,136] ZrO nanoparticles, [137] titanium dioxide nanoparticles [138] and CuS nanoparticles.…”
Section: Nanomaterials For Enhancing Mechanical Propertiesmentioning
confidence: 99%
“…Some studies have also found that nanoparticles of different particle diameters [ 132 ] and shapes can affect the mechanical properties of materials. Besides, researchers often use metal nanoparticles to enhance the mechanical properties of polymer materials, [ 133 ] such as Fe 2 O 3 nanoparticles, [ 134 ] gold nanoparticles, [ 135,136 ] ZrO nanoparticles, [ 137 ] titanium dioxide nanoparticles [ 138 ] and CuS nanoparticles.…”
Section: Incorporation Of Nanomaterials Into 3d‐printed Productsmentioning
confidence: 99%